ANALISIS UJI PRODUKSI DENGAN ORIFICE PLATE PADA SUMUR J-97 LAPANGAN PANAS BUMI “KYU” - Samsol Samsol; Widia Yanti; Onnie Ridaliani Ridaliani; Stiven Julian (PETRO:Jurnal Ilmiah Teknik Perminyakan, 2019)
In a study entitled "Analysis of Production Tests with Orifice Plate on the J-97 Well KYU Geothermal Field" will discuss the production test. Geothermal production tests are conducted to determine the potential of the production capacity of a well at different wellhead pressures so that the value of the mass flow rate and the well production curve is obtained. J-97 well is one-phase steam well, so the production test method used is to use the orifice plate. The pressure data read by the orifice plate is then converted to a mass flow rate. Calculating the mass flow rate can use the British Standard 1042 method. In the production test to obtain the final result in the form of a production curve, the gas deliverability equation can be used. The method used in the S-87 well is Flow After Flow Test (Back pressure Test). The final result of the curve shows a decrease in the production line calculated using the British Standard 1042 method..